Aplikasi Supply Chain Operation Reference (SCOR) pada Produk Chocodot PT Tama Cokelat Garut Indonesia - Nur Hasanah; Vita Sarasi; Ina Primiana (Universitas Mercu Buana, 2022)
This study applies the SCOR (Supply Chain Operations Reference) method at one of the companies engaged in the Food and Beverage (F&B) sector, namely PT. Chocolate Tama. The goal is to determine the level of importance of the company's five main activities, namely Plan, Source, Make, Deliver and Return so as to measure and improve the company's total supply chain performance. The research begins with determining KPIs and Supply Chain Management Metrics and weighting supply chain management metrics Level I, II and III using AHP. The results of the validation process there are 44 metrics that represent the performance of supply chain activities, namely 11 plan metrics, 10 source metrics, 7 make metrics, 10 deliver metrics and 6 return metrics. The plan activity has the highest weight value of 0.3188, after that successively source is 0.2254, deliver is 0.1560, make is 0.1511 and return is 0.1487. There are 21 sequences of supply chain performance metrics that must be improved so that there are no more delays in the supply of raw materials as well as recommendations for improvement for increasing the company's revenue in the future. The first three sequences that have the highest values that need to be improved are plan source (planning the source of raw materials), forecast accuracy (forecasting accuracy) and purchase order cycle time (determination of purchase order cycle time).